1997
DOI: 10.1002/(sici)1099-1581(199707)8:7<381::aid-pat660>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Heterolayer light-emitting diodes based on poly-phenylene vinylene

Abstract: In order to enhance the quantum efficiency of poly‐p‐phenylene vinylene (PPV) light‐emitting diodes (LEDs), we have fabricated metal/insulator/polymer (MIP) LEDs and heterolayer LEDs based on PPV and oxadiazole polymers. The current–voltage (I–V) characteristics and electroluminescence (EL) intensity of the MIP structures display a pronounced dependence of the insulator thickness and we detect an increase in the quantum efficiency of more than a factor of 30 at an AlOx layer thickness of 3–6 nm. The device cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The HOMO level variation of PTtx‐O according to alkyl side‐chain lengths roughly agrees with the results from electrochemical measurement. As it has been common practice to estimate LUMO level by subtraction of the optical bandgap from HOMO level determined either electrochemically or via optical absorption spectra,40–42 here we show the energy band diagram derived from UPS and UV–vis measurement [Fig. 7(a)] and band diagram derived from electrochemical measurement [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The HOMO level variation of PTtx‐O according to alkyl side‐chain lengths roughly agrees with the results from electrochemical measurement. As it has been common practice to estimate LUMO level by subtraction of the optical bandgap from HOMO level determined either electrochemically or via optical absorption spectra,40–42 here we show the energy band diagram derived from UPS and UV–vis measurement [Fig. 7(a)] and band diagram derived from electrochemical measurement [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent papers, it was reported that the introduction of ionic materials such as LiF [7] and CaO [8] at the interface between a metal cathode and an organic layer enhances electron injection from cathode, resulting in improved EL efficiency in the organic LED. It was also reported that the introduction of good inorganic insulating materials such as AlOx [9,10] and SiO [11] at the interface enhances the EL efficiency. It is interesting and significant to clarify the carrier transfer behaviour at the inorganic-organic and organic-organic interfaces.…”
Section: Introductionmentioning
confidence: 97%